Implementasi Pengolahan Dokumen Menggunakan VBA dan Microsoft Excel - Kristia Yuliawan; Juridno Wilson (STMIK Pesat Nabire, 2024)
Efficient data management is essential for organizations, especially in the face of large volumes of data. Digitization of archives through document collection, scanning, and manipulation can improve operational efficiency, reduce the risk of data loss, and facilitate information access. operational efficiency, reduce the risk of data loss, and facilitate access to information. This research focuses on implementation of a document classification system in BKPSDM Nabire using VBA and Microsoft Excel to improve efficiency of data processing. The method used is the waterfall model, which includes the needs analysis stage, system design, implementation, and testing. The results of the analysis show that manual document management has many weaknesses, such as difficulty in conveying information and lack of supporting applications. Solution The proposed solution is a Visual Basic and Excel-based system, which enables automatic document processing, improve data accuracy and consistency, as well as facilitate search and decision making. System testing using the black-box method shows valid results, ensuring that the system runs according to the expected functional specifications. functional specifications. The implementation of this system is expected to make a significant contribution in improving the efficiency, accuracy, and productivity of document management. efficiency, accuracy, and productivity of document management in BKPSDM Kabupaten Nabire.